Pengaruh pemberian ekstrak herba meniran (phyllanthus niruri, l.) terhadap ukuran dan struktur histologik kelenjar prostat tikus jantan (rattus norvegicus, l.) - Ciptono '; Tri Harjana (Jurnal Sains Dasar, 2013)
Abstract Meniran (Phyllanthus niruri, L.) known as a beneficial rich plant. This research aimed to see its influence to size measured and histological structure of male mouse prostate gland (Rattus norvegicus, L.). Adult male white rat, 24 heads, age ±2,5 months, divided to become six treatment groups covering: A (control), B (placebo), C (0,7 mg/200g bw), D (0,9 mg/200g bw), E (1,8 mg/200g bw) and F (2,7 mg/200g bw). Treatment of herb meniran extract per oral counted 2,0 ml/day during 49 days (one cycle of rat spermatogenesis). Research conducted in LP3HP UGM, animal house, and histology laboratory of Biology Education Department FMIPA UNY. On day-50, each treatment killed and cut open to be taken its prostate gland, then diameter of this organ measured, fixated, and processed for the making of microanatomical slide preparats with paraffin method. Data covered the prostate glands weight and diameter, tested with Analysis Variance (ANOVA = 0,01 or 0,05), then continued with Duncan’s Test (DMRT). Qualitative analysis conducted on histological structure of prostate glands and presented on microphotographs. Result of research showed that extract of meniran influenced the size of male white rat prostate gland. The higher concentration tend to degrade prostate gland diameter size. Extract of meniran have a qualitative effect on histological structure of male rat prostate gland. This showed from  the higher extract concentration give influence progressively thickness lost of lobular epitel wall and decreasing of mass secretions in the prostate gland luminal.   Keywords: rat, prostate gland, meniran, histology.